Complexation of Bis-2-(benzylideneamino) Phenol to Cobalt (II) and Zinc (II), and their Spectroscopic Studies - MENG GUAN, TAY,; ZAINAB, NGAINI; MAYA ASYIKIN, MOHD ARIF; EMELIA, ENGGIE (Borneo Journal of Resource Science and Technology, 2013)
A bis-Schiff base of bis-2-(benzylideneamino)phenol (SB1) was synthesized via condensation reaction of terephthaldehyde and 2-aminophenol in ethanol. SB1 was then reacted with respective MX2 salt (M = Co & Zn, X = Cl & OAc) in the ligand to metal ratio of 1:2 under refluxing condition in ethanolic KOH solution for six hours. All synthesized complexes were characterized using FT-IR and UV-vis spectroscopy. The formation of complexes with Co and Zn was indicated by the shifts observed from the IR peaks and λmax of the UV absorption bands for the C=N bond. The IR peak at 1621 cm-1 in SB1 was shifted to around 1638 and 1619 cm-1 after forming its complexes with Co and Zn, respectively. The absorption band of C=N bond was blue shifted from λmax of 384 nm to 307 nm in Co(II) complex, whereas this band was red-shifted to 389 nm in the Zn(II) complex. Therefore, SB1 was confirmed to coordinate with the Co(II) and Zn(II) metal centres via the imine nitrogen.